Conductive silver paste, method for preparing back electrode of solar cell and solar cell

By using conductive silver paste and glass paste with high content of conductive silver powder to form an outer protective layer, the problem of stability and service life of solar cells in low-rail space environment is solved, and a high density and high conductivity solar cell back electrode is achieved.

CN119833201AActive Publication Date: 2025-04-15LUCKY FILM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411995588.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The stability and service life of solar cells on low-orbit space vehicles are affected by factors such as space radiation, temperature changes and aging of metal electrodes, resulting in material defects, shedding and aging.

Method used

Conductive silver paste with high content of conductive silver powder is used as the preparation slurry for the back electrode of the solar cell. By optimizing the specific surface area and sintering activity of the silver powder, combined with the synergistic effect of the glass powder and the organic carrier, a high density and high conductivity silver main gate is prepared, and the glass paste is printed on the aluminum sub gate to form an outer protective layer to reduce metal mixing and aging.

Benefits of technology

It improves the stability and service life of the electrode on the back of the solar cell, enhances its welding performance and conductivity, and reduces the occurrence of aging and powder loss problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224468910000091
    Figure BDA0005224468910000091
  • Figure HDA0005224468920000011
    Figure HDA0005224468920000011
  • Figure HDA0005224468920000012
    Figure HDA0005224468920000012
Patent Text Reader

Abstract

The invention relates to the field of solar cells, and discloses conductive silver paste, a method for preparing a back electrode of a solar cell and the solar cell. The conductive silver paste comprises 50-90 parts by mass of conductive silver powder, 0.5-10 parts by mass of glass powder, 1-20 parts by mass of an organic carrier, 2-20 parts by mass of a solvent and 0.5-10 parts by mass of an auxiliary agent, and the specific surface area of the conductive silver powder is 1.0 m < 2 > / g-1. 5 m < 2 > / g. The conductive silver paste provided by the invention can be used as preparation paste of a main silver grid of a back electrode of a solar cell, can improve the welding performance and the conductivity of the back electrode of the solar cell, and is beneficial to improving the stability of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solar cells, and in particular, to a conductive silver paste, a method for preparing a back electrode of a solar cell, and a solar cell. Background Art

[0002] Solar cells are one of the most commonly used power sources for low-orbit spacecraft. They are widely used in various types of satellites, space stations and other spacecraft as their main source of electricity. For example, the International Space Station uses a large number of solar cells to meet its power needs. Solar cells used in low-orbit spacecraft have high performance reliability and controllable manufacturing costs as a power source. However, there are many environmental factors in the low-orbit space environment that can cause continuous damage to solar cells and limit the service life of solar cells, such as the huge temperature changes between the sun-facing and shaded states during the movement around the earth, and continuous radiation damage in space. Therefore, in order to further improve the performance of solar cells on low-orbit spacecraft, it is necessary to continue to study the materials and structures of solar cells. Summary of the invention

[0003] In the first aspect of the present application, the present application proposes a conductive silver paste, comprising: 50 to 90 parts by mass of conductive silver powder, 0.5 to 10 parts by mass of glass powder, 1 to 20 parts by mass of an organic carrier, 2 to 20 parts by mass of a solvent, and 0.5 to 10 parts by mass of an auxiliary agent, wherein the specific surface area of ​​the conductive silver powder is 1.0 m 2 / g-1.5m 2 / g.

[0004] The conductive silver paste proposed in this application can be used as a slurry for preparing the silver main grid of the back electrode of a solar cell. The conductive silver paste has a high content of conductive silver powder, and by limiting the specific surface area of ​​the conductive silver powder, the synergistic relationship between the sintering activity of the conductive silver powder and other components is optimized. As a result, the conductive silver paste can be used to prepare a high-reliability, low-resistivity back electrode of a solar cell, improve the welding performance and conductivity of the back electrode of the solar cell, and help improve the stability of the solar cell.

[0005] In some embodiments, the conductive silver paste includes: 75-85 parts by mass of conductive silver powder, 1-5 parts by mass of glass powder, 1-10 parts by mass of organic vehicle, 2-20 parts by mass of solvent, and 1-5 parts by mass of additives.

[0006] In some embodiments, the silver content of the conductive silver paste is 75%-85%. Therefore, the conductive silver paste has a high conductivity.

[0007] In some embodiments, the Dv50 particle size of the conductive silver powder is 0.5 μm-1.5 μm, and the tap density of the conductive silver powder is 3 g / cm 3 -10g / cm 3 As a result, the back electrode of the solar cell prepared by the conductive silver paste has better structural density and higher conductivity.

[0008] In some embodiments, the sintering temperature of the conductive silver powder is 200° C.-300° C. Therefore, the conductive silver powder has a relatively high sintering activity, which is beneficial to improving the compactness of the silver main grid prepared after sintering the conductive silver paste.

[0009] In some embodiments, the glass powder includes at least one of Te2O-Bi2O3-PbO glass, PbO-SiO2 glass powder, and lead-free glass powder, and the Dv50 particle size of the glass powder is 0.5 μm-10 μm. The aforementioned glass powder has a certain promoting effect on the sintering of the conductive silver powder in the conductive silver paste, thereby helping to improve the sintering performance of the conductive silver paste.

[0010] In some embodiments, the organic carrier includes at least one of ethyl hydroxyethyl cellulose, nitrocellulose, a mixture of ethyl cellulose and phenolic resin, alkyd resin, phenolic resin, acrylate resin, xylene resin, polybutylene resin, polyester resin, urea resin, vinyl acetate resin, wood rosin or polymethacrylate of alcohol. Thus, the aforementioned organic carrier can give the conductive silver paste a viscosity and rheological properties suitable for screen printing processing.

[0011] In some embodiments, the solvent includes at least one of diethylene glycol diethyl ether, butyl carbitol (diethylene glycol monobutyl ether), diethylene glycol butyl ether acetate, carbitol butyl ether acetate, etc., diacetone alcohol, terpineol, benzyl alcohol, cyclohexanone, methyl ethyl ketone, dibasic acid ester, 2,2,4-trimethyl 1,3-pentanediol monoisobutyl ester, and 2,2,4-trimethyl 1,3-pentanediol diisobutyl ester. Thus, the aforementioned solvent can improve the fluidity of the conductive silver paste to prepare the back electrode of the solar cell.

[0012] In some embodiments, the auxiliary agent includes a dispersant, and the dispersant includes at least one of sorbitan trioleate, dimethylacetamide, TDO, BYK-110 and BYK-111. The above dispersant can reduce the agglomeration of the conductive silver powder, so that the conductive silver paste can be printed more smoothly through the screen. This is conducive to improving the quality of screen printing.

[0013] In the second aspect of the present application, a method for preparing the back electrode of a solar cell using the conductive silver paste proposed in the present application is characterized in that it includes: using the conductive silver paste to perform a first screen printing process on the surface of the solar cell back panel to obtain a solar cell back panel printed with a silver paste main grid; drying and sintering the solar cell back panel printed with the silver paste main grid in sequence to obtain a solar cell back panel printed with a silver main grid; using aluminum paste to perform a second screen printing process and drying process on the solar cell back panel printed with the silver main grid to obtain a solar cell back panel printed with an aluminum sub-grid; covering the aluminum sub-grid with printed glass paste, and drying and sintering in sequence to prepare the back electrode of the solar cell.

[0014] This method first prints and prepares the silver main grid, then prints and prepares the aluminum sub-grid, and prints glass paste on the aluminum sub-grid and performs sintering treatment to prepare an outer protective layer covering the aluminum sub-grid. This method can reduce the formation of silver-aluminum metal mixed crystals. The glass paste printed on the overlapping part of the silver main grid and the aluminum sub-grid also protects the overlapping part of the silver main grid and the aluminum sub-grid, and can reduce the accelerated aging during service caused by the difference in thermal expansion coefficient and crystal structure between silver and aluminum metals, protect the aluminum sub-grid and the silver-aluminum overlapping part, and help reduce the occurrence of aging and powdering problems at the overlapping part of the silver electrode and the aluminum electrode. Therefore, the back electrode of the solar cell prepared by the method proposed in this application has better stability and longer service life.

[0015] In some embodiments, the mesh number of the screen plate processed by the first screen printing is 200-300 meshes, thereby printing a line pattern of a silver main grid with uniform width and neat edges, which helps to improve the performance and appearance quality of the back electrode of the solar cell.

[0016] In some embodiments, the mesh number of the screen plate processed by the second screen printing is 300-400 meshes, which is conducive to preparing an aluminum sub-grid with clear edge lines and improving the current collection performance.

[0017] In the third aspect of the present application, the present application proposes a solar cell, wherein the solar cell adopts the conductive silver paste proposed in the present application to prepare the silver main grid, or includes the back electrode of the solar cell prepared by the method proposed by the present application.

[0018] The solar cell proposed in the present application has a high stability of the back cell of the solar cell, which is beneficial to improving the conductivity and service life of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0020] Figure 1A unit design pattern of a silver main grid of a back electrode of a solar cell in one embodiment of the present application;

[0021] Figure 2 This is a unit design pattern of the aluminum sub-grid of the back electrode of a solar cell in one embodiment of the present application. DETAILED DESCRIPTION

[0022] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0023] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0024] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0025] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0026] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0027] Solar cells convert solar energy into electrical energy and are the source of power for low-orbit spacecraft. Among them, solar cells that can be used for low-orbit spacecraft include p-type passivated emitter and back contact solar cells (p-PERC cells). Conductive slurries can be used for screen printing to prepare the back electrode of the solar cell on the backlight side of the p-PERC cell. This method helps to significantly reduce manufacturing costs. However, there is space radiation in the low-orbit space environment, and the back electrode of the solar cell is bombarded by high-energy particles, causing defects in the back electrode material of the solar cell, and the environmental stability changes dramatically with the change of the motion trajectory. During the use of solar cells, the back electrode of the solar cell may fall off or peel off due to decreased adhesion, affecting the long-term stability and reliability of the battery.

[0028] In order to improve the stability of the back electrode of a solar cell, the present application proposes a conductive silver paste and a method for preparing the back electrode of a solar cell, by adjusting the composition of the conductive silver paste to increase its silver content, thereby improving the structure and performance of the back electrode of a solar cell prepared using the conductive silver paste. In addition, a method for preparing the back electrode of a solar cell using the conductive silver paste is also proposed, thereby improving the stability of the prepared back electrode of the solar cell.

[0029] In the first aspect of the present application, the present application proposes a conductive silver paste, comprising: 50 to 90 parts by mass of conductive silver powder, 0.5 to 10 parts by mass of glass powder, 1 to 20 parts by mass of an organic carrier, 2 to 20 parts by mass of a solvent, and 0.5 to 10 parts by mass of an auxiliary agent, wherein the specific surface area of ​​the conductive silver powder is 1.0 m 2 / g-1.5m 2 / g.

[0030] The conductive silver paste proposed in this application can be used as a preparation slurry for the silver main grid of the back electrode of a solar cell. The conductive silver paste has a high content of conductive silver powder. By limiting the specific surface area of ​​the conductive silver powder, the conductive silver paste still has a high fluidity when the silver content in the conductive silver paste is high. By optimizing the synergistic relationship between the sintering activity of the conductive silver powder and other components, the film-forming temperature of the sintering change of the conductive silver powder is matched with the decomposition temperature of the organic carrier and the solvent in the conductive silver paste, so that the conductive silver paste can be used to prepare the back electrode of a solar cell with high electrode density through screen printing and sintering, reducing the occurrence of problems such as electrode blistering and electrode shedding. Therefore, the silver main grid of the back electrode of the solar cell prepared by the conductive silver paste can have a dense microstructure and a high surface smoothness, which is conducive to forming an ohmic contact with the back panel of the solar cell. As a result, the conductive silver paste can prepare a high-reliability, low-resistivity back electrode of a solar cell, improve the welding performance and conductivity of the back electrode of the solar cell, and help improve the stability of the solar cell.

[0031] In some embodiments, the conductive silver paste includes: 75-85 parts by mass of conductive silver powder, 1-5 parts by mass of glass powder, 1-10 parts by mass of organic vehicle, 2-20 parts by mass of solvent, and 1-5 parts by mass of additives.

[0032] In some embodiments, the silver content of the conductive silver paste is 75%-85%. Therefore, the conductive silver paste has a high conductivity.

[0033] In some embodiments, the Dv50 particle size of the conductive silver powder is 0.5 μm-1.5 μm, and the tap density of the conductive silver powder is 3 g / cm 3 -10g / cm 3 The shapes of the conductive silver powder include spherical silver powder and irregular flaky silver powder. The Dv50 particle size and tap density of the conductive silver powder are within the aforementioned ranges. In the silver paste sintering process for preparing the back electrode of the solar cell with the conductive silver paste, it is also beneficial for the conductive silver powder to be mixed with the glass powder and sintered to form a glass phase with a relatively continuous and uniform silver content. As a result, the back electrode of the solar cell prepared with the conductive silver paste has a better structural density and a higher conductivity.

[0034] In some embodiments, the sintering temperature of the conductive silver powder is 200° C.-300° C. Therefore, the conductive silver powder has a relatively high sintering activity, which is beneficial to improving the compactness of the silver main grid prepared after sintering the conductive silver paste.

[0035] In some embodiments, the glass powder includes at least one of Te2O-Bi2O3-PbO glass, PbO-SiO2 glass powder, and lead-free glass powder, and the Dv50 particle size of the glass powder is 0.5μm-10μm. The sintering of the aforementioned glass powder has a certain promoting effect on the sintering of the conductive silver powder in the conductive silver paste, so that while the conductive silver powder undergoes sintering changes, the glass powder softens and further mixes and sinters with the conductive silver powder, and is beneficial to improving the adhesion of the conductive silver paste on the surface of the solar back panel. Its Dv50 particle size is within the aforementioned range, which is conducive to mixing and dispersing with the conductive silver powder. As a result, it is beneficial to improve the sintering performance of the conductive silver paste.

[0036] In some embodiments, the organic carrier includes at least one of ethyl hydroxyethyl cellulose, nitrocellulose, a mixture of ethyl cellulose and phenolic resin, alkyd resin, phenolic resin, acrylate resin, xylene resin, polybutylene resin, polyester resin, urea resin, vinyl acetate resin, wood rosin or polymethacrylate of alcohol. Thus, the aforementioned organic carrier can give the conductive silver paste a viscosity and rheological properties suitable for screen printing processing.

[0037] In some embodiments, the solvent includes at least one of diethylene glycol diethyl ether, butyl carbitol (diethylene glycol monobutyl ether), diethylene glycol butyl ether acetate, carbitol butyl ether acetate, etc., diacetone alcohol, terpineol, benzyl alcohol, cyclohexanone, methyl ethyl ketone, dibasic acid ester, 2,2,4-trimethyl 1,3-pentanediol monoisobutyl ester, and 2,2,4-trimethyl 1,3-pentanediol diisobutyl ester. Thus, the aforementioned solvent can improve the fluidity of the conductive silver paste to prepare the back electrode of the solar cell.

[0038] In some embodiments, the auxiliary agent includes a dispersant, and the dispersant includes at least one of sorbitan trioleate, dimethylacetamide (DMA), TDO, BYK-110 and BYK-111. TDO is Nouryon Duomeen TDO dispersant, and BYK-110 and BYK-111 are dispersants produced by German BYK. The aforementioned dispersant can reduce the agglomeration of the conductive silver powder, so that the conductive silver paste can be printed more smoothly through the screen. This is conducive to improving the quality of screen printing.

[0039] In the second aspect of the present application, a method for preparing the back electrode of a solar cell using the conductive silver paste proposed in the present application is characterized in that it includes: using the conductive silver paste to perform a first screen printing process on the surface of the solar cell back panel to obtain a solar cell back panel printed with a silver paste main grid; drying and sintering the solar cell back panel printed with the silver paste main grid in sequence to obtain a solar cell back panel printed with a silver main grid; using aluminum paste to perform a second screen printing process and drying process on the solar cell back panel printed with the silver main grid to obtain a solar cell back panel printed with an aluminum sub-grid; covering the aluminum sub-grid with printed glass paste, and drying and sintering in sequence to prepare the back electrode of the solar cell.

[0040] The method for preparing the back electrode of a solar cell proposed in this application is referred to Figure 1 The first screen printing process includes screen printing the conductive silver paste onto the solar cell back panel through a screen plate, and the printed pattern and the width of the printed silver paste main grid can be controlled. Through the sintering process, the conductive silver paste printed on the solar cell back panel forms a silver main grid. Figure 2 , the second screen printing process includes screen printing aluminum paste onto the back panel of the solar cell through a screen plate, the pattern position of the aluminum paste printing overlaps with the silver main grid, and part of the aluminum paste is printed on the surface of the silver main grid to form a stacked layer overlapping each other. Through a drying process, the aluminum paste printed on the solar back panel forms an aluminum sub-grid. The glass paste covering the printed aluminum sub-grid can be sintered to cover the aluminum sub-grid in a glass paste layer formed by the glass paste to form an outer protective layer of the aluminum sub-grid. This method first prints to prepare the silver main grid, then prints to prepare the aluminum sub-grid, and prints glass paste on the aluminum sub-grid to prepare an outer protective layer covering the aluminum sub-grid.

[0041] This method first prints and prepares the silver main grid, then prints and prepares the aluminum sub-grid, and prints glass paste on the aluminum sub-grid and performs sintering treatment to prepare an outer protective layer covering the aluminum sub-grid. This method can reduce the formation of silver-aluminum metal mixed crystals. The glass paste printed on the overlapping part of the silver main grid and the aluminum sub-grid also protects the overlapping part of the silver main grid and the aluminum sub-grid, and can reduce the accelerated aging during service caused by the difference in thermal expansion coefficient and crystal structure between silver and aluminum metals, protect the aluminum sub-grid and the silver-aluminum overlapping part, and help reduce the occurrence of aging and powdering problems at the overlapping part of the silver electrode and the aluminum electrode. Therefore, the back electrode of the solar cell prepared by the method proposed in this application has better stability and longer service life.

[0042] In some embodiments, the sintering process is performed at a temperature of 500°C-900°C.

[0043] Sintering in the aforementioned temperature range can remove organic components such as solvents in the conductive silver paste, so that the particles of the conductive silver powder in the conductive silver paste melt and undergo metal fusion to form a complete silver main grid structure, which is conducive to forming a silver main grid with a denser microstructure and a smoother surface. In addition, during the sintering process, a chemical bond is formed between the silver main grid and the solar cell back panel, so that the silver main grid can be firmly attached to the solar cell back panel, thereby improving the silver main grid structure, increasing the bonding force between the silver main grid and the solar cell back panel, and helping to reduce the shedding or peeling phenomenon of the silver main grid.

[0044] Sintering the glass paste within the aforementioned temperature range can soften the glass particles in the glass paste, reduce viscosity, and flow to form a dense layered structure. In the present application, the glass paste is printed to cover the aluminum sub-grid. During the sintering process, the glass paste forms a glass film layer to fill the pores on the surface of the aluminum sub-grid and cover the overlap between the aluminum sub-grid and the silver main grid. This is beneficial to improve the stability of the aluminum sub-grid structure, reduce the formation of silver-aluminum mixed crystals, enhance the stability of the adhesion between the aluminum sub-grid and the solar cell back panel, and reduce aging phenomena such as powder loss.

[0045] In some embodiments, the sintering process includes a gradient sintering process.

[0046] In some embodiments, the drying process is performed at a temperature of 150°C-250°C.

[0047] In some embodiments, the method for preparing glass paste includes: premixing 25 parts by mass of lead-free glass powder, 15 parts by mass of ethyl cellulose resin, and 60 parts by mass of solvent diethylene glycol butyl ether acetate with a planetary stirring degassing machine, and then rolling with a three-roll mill until the fineness reaches less than 10 μm to prepare glass paste.

[0048] In some embodiments, the mesh number of the screen plate of the first screen printing process is 200-300 meshes. The first screen printing process includes printing a conductive silver paste on the back panel of the solar cell. The mesh number of the screen plate is within the aforementioned range. The conductive silver paste can pass through the mesh of the screen plate screen more easily, and the screen printing accuracy is high. Thus, a line pattern of a silver main grid with uniform width and neat edges can be printed, which helps to improve the performance and appearance quality of the back electrode of the solar cell.

[0049] In some embodiments, the mesh number of the screen plate for the second screen printing process is 300-400 mesh. The second screen printing process includes printing aluminum paste on the solar cell backplane, and the mesh number of the screen plate is within the aforementioned range, which can reduce the situation of blurred printing, broken lines or uneven thickness. This is conducive to preparing an aluminum sub-grid with clear edge lines and improving current collection performance.

[0050] In the third aspect of the present application, the present application proposes a solar cell, wherein the solar cell adopts the conductive silver paste proposed in the present application to prepare the silver main grid, or includes the back electrode of the solar cell prepared by the method proposed by the present application.

[0051] The solar cell proposed in the present application includes a p-type passivated emitter and a back contact solar cell (p-PERC cell). The silver main grid in the back electrode of the solar cell prepared by the conductive silver paste proposed by the present application can improve the electrode density and surface smoothness of the silver main grid, thereby improving the welding performance and conductivity of the p-PERC cell electrode. The back electrode of the solar cell is prepared by the method proposed in the present application, and the glass paste forms an outer protective layer, which reduces the occurrence of aging and powdering, improves the stability of the back cell of the solar cell, and is beneficial to improving the conductivity and service life of the solar cell.

[0052] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0053] Example 1

[0054] S1: 80 parts by mass of spherical silver powder (average particle size 1 μm, tap density 5 g / cm 3 -6g / cm 3, sintering temperature 200°C-300°C), 2 parts by mass of PbO-SiO2 glass powder, 3 parts by mass of ethyl cellulose resin, 14 parts by mass of solvent diethylene glycol butyl ether acetate, and 1 part by mass of auxiliary agent BYK-111 are pre-mixed with a planetary stirring degassing machine and then rolled with a three-roll mill to a fineness of less than 10μm to prepare a conductive silver paste with a silver content of 80%.

[0055] S2: Use a screen printer to print conductive silver paste and aluminum paste on the back panel of a TCO / Si solar cell at a blade pressure of 0.18 MPa according to the unit design pattern of the back electrode of the solar cell: print the conductive silver paste on the back panel of the solar cell, dry and sinter it, then overlap and print the aluminum paste, dry it, and then laminate and print the glass paste on the aluminum paste, dry it and sinter it to prepare the back electrode of the solar cell.

[0056] Comparative Example 1

[0057] S1: 80 parts by mass of spherical silver powder (average particle size 1 μm, tap density 5 g / cm 3 -6g / cm 3 , sintering temperature 200°C-300°C), 2 parts by mass of PbO-SiO2 glass powder, 3 parts by mass of ethyl cellulose resin, 14 parts by mass of solvent diethylene glycol butyl ether acetate, and 1 part by mass of auxiliary agent BYK-111 are pre-mixed with a planetary stirring degassing machine and then rolled with a three-roll mill to a fineness of less than 10μm to prepare a conductive silver paste with a silver content of 80%.

[0058] S2: Use a screen printer to print traditional silver paste and aluminum paste on the TCO / Si solar cell back panel at a scraper pressure of 0.18 MPa according to the unit design pattern of the back electrode of the solar cell: print the traditional silver paste on the solar cell back panel, dry and sinter it, then overlap and print the aluminum paste, dry and sinter it, to prepare the back electrode of the solar cell.

[0059] Comparative Example 2

[0060] S1: Uses conventional silver paste with a silver content of 65%.

[0061] S2: Use a screen printer to print conductive silver paste and aluminum paste on the back panel of a TCO / Si solar cell at a blade pressure of 0.18 MPa according to the unit design pattern of the back electrode of the solar cell: print the conductive silver paste on the back panel of the solar cell, dry and sinter it, then overlap and print the aluminum paste, dry it, and then laminate and print the glass paste on the aluminum paste, dry it and sinter it to prepare the back electrode of the solar cell.

[0062] Test method:

[0063] 1. Welding tensile test

[0064] Use desktop welding equipment FJL2023001, set the pressure to 8N; set the voltage to 0.7V. Fix the battery with welded tensile test piece or interconnection piece on the tester. The tensile test piece should be bent upward to 45° and clamped with a chuck. The force direction is 135° to the solar cell. Use the following two methods to determine the tensile strength of the solder joint. The rate of force applied to the tensile test piece is not more than 1N / s. At the moment when the tensile piece is pulled off the battery, record the indicated tensile reading.

[0065] 2. Steady-state damp heat test

[0066] Perform steady-state damp heat tests in the following order:

[0067] a) Measure electrical performance before testing;

[0068] b) Place the battery in the sample rack, and then place the sample rack in a damp heat test chamber. The temperature of the damp heat test chamber is 60℃±2℃, and the relative humidity is not less than 90%, and it is maintained for 96 hours. The sample rack and damp heat test chamber should meet the following requirements:

[0069] 1) Battery samples and sample holder materials do not react chemically under wet and hot conditions; 2) Condensed water on the walls and top of the wet and hot test chamber should not fall on the battery; 3) The wet source water used in the wet and hot test chamber is deionized water; 4) The sample holder and wet and hot test chamber should not bring corrosive pollutants to the battery.

[0070] c) After the test, first check the battery appearance and mechanical defects;

[0071] d) Conduct an electrode firmness test and check for electrode defects. Use a tape with a peel strength of not less than 3.4N / cm between the clean steel surface to cover the upper and lower surfaces of the solar cell. Rub the tape until there is no foggy blank and the solar cell is firmly adhered. Then peel off the tape at an angle of 0° to 90° to the surface of the solar cell. The anti-reflection film of the cell should not have blanks with a diameter greater than 1.8mm; blanks with a diameter of 0.6mm-1.8mm should not exceed 5 per square centimeter; blanks with a diameter less than 0.6mm can be ignored. Blanks caused by the coating fixture are allowed, but the blank area should not be greater than 1% of the total cell area.

[0072] Test results: See Table 1.

[0073] Table 1

[0074]

[0075] As shown in Table 1, the conductive silver paste proposed in this application can improve the welding tension of the back electrode of the solar cell and reduce the resistance, so that the printed back electrode of the solar cell is more firmly attached and the electrical performance of the back plate electrode of the solar cell is improved. The method for preparing the back electrode of the solar cell proposed in this application can improve the stability of the back electrode of the solar cell and reduce aging and powder loss.

[0076] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0077] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0078] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0079] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A conductive silver paste, characterized in that: include: 50-90 parts by mass of conductive silver powder, 0.5-10 parts by mass of glass powder, 1-20 parts by mass of organic carrier, 2-20 parts by mass of solvent, and 0.5-10 parts by mass of auxiliary agent, wherein the specific surface area of ​​the conductive silver powder is 1.0 m 2 / g-1.5m 2 / g.

2. The conductive silver paste according to claim 1, characterized in that: 75 to 85 parts by mass of conductive silver powder, 1 to 5 parts by mass of glass powder, 1 to 10 parts by mass of organic carrier, 2 to 20 parts by mass of solvent, and 1 to 5 parts by mass of auxiliary agent.

3. The conductive silver paste according to claim 1 or 2, characterized in that: The silver content in the conductive silver paste is 75%-85%.

4. The conductive silver paste according to claim 1 or 2, characterized in that: The Dv50 particle size of the conductive silver powder is 0.5 μm-1.5 μm, and the tap density of the conductive silver powder is 3 g / cm 3 -10g / cm 3 .

5. The conductive silver paste according to claim 1 or 2, characterized in that: The sintering temperature of the conductive silver powder is 200°C-300°C.

6. The conductive silver paste according to claim 1 or 2, characterized in that: The glass powder comprises at least one of Te2O-Bi2O3-PbO glass, PbO-SiO2 glass powder and lead-free glass powder, and the Dv50 particle size of the glass powder is 0.5 μm-10 μm; and / or, The organic carrier includes at least one of ethyl hydroxyethyl cellulose, nitrocellulose, a mixture of ethyl cellulose and phenolic resin, alkyd resin, phenolic resin, acrylate resin, xylene resin, polybutene resin, polyester resin, urea resin, vinyl acetate resin, wood rosin or polymethacrylate of alcohol.

7. The conductive silver paste according to claim 1 or 2, characterized in that: The solvent includes at least one of diethylene glycol diethyl ether, butyl carbitol (diethylene glycol monobutyl ether), diethylene glycol butyl ether acetate, carbitol butyl ether acetate, diacetone alcohol, terpineol, benzyl alcohol, cyclohexanone, methyl ethyl ketone, dibasic acid ester, 2,2,4-trimethyl 1,3-pentanediol monoisobutyl ester, and 2,2,4-trimethyl 1,3-pentanediol diisobutyl ester; and / or, The auxiliary agent includes a dispersant, and the dispersant includes at least one of sorbitan trioleate, dimethylacetamide, TDO, BYK-110 and BYK-111.

8. A method for preparing a back electrode of a solar cell using the conductive silver paste according to any one of claims 1 to 7, characterized in that: include: Conductive silver paste is used to perform a first screen printing process on the surface of the solar cell back plate to obtain a solar cell back plate with a silver paste main grid printed thereon; The solar cell back panel printed with the silver paste main grid is subjected to a drying treatment and a sintering treatment in sequence to obtain a solar cell back panel printed with the silver main grid; A second screen printing process and a drying process are performed on the solar cell back panel printed with the silver main grid using aluminum paste to obtain a solar cell back panel printed with aluminum auxiliary grid; The aluminum auxiliary grid is covered with printed glass paste, and then dried and sintered in sequence to prepare the back electrode of the solar cell.

9. The method according to claim 8, characterized in that The mesh number of the screen plate for the first screen printing process is 200-300 mesh; and / or, The mesh number of the screen plate processed by the second screen printing is 300-400 meshes.

10. A solar cell, characterized in that: The solar cell adopts the conductive silver paste described in any one of claims 1 to 7 to prepare the back electrode of the solar cell, or includes the back electrode of the solar cell prepared by the method described in claim 8 or 9.

Citation Information

Patent Citations

  • Lead-free environmentally-friendly silver paste and method for forming back electrode of silicon solar cell

    CN102222705A

  • Perforated PERC double-face solar battery and assembly, system and preparation of said solar battery

    CN106847943A

  • Solar cell Al grid line structure and preparation method thereof

    CN110047952A

  • Main grid silver paste for silicon solar cell and preparation method thereof

    CN114843005A

  • Electrode paste composition for rear surface of solar cell

    WO2011074888A2